How an "Onaya Dreams": A Healer's Affinal Relationship With Plants - Watanabe, Yumi (Anthropology of consciousness, 2025)
Healers of the Shipibo, known as onayas, reside in Eastern Peru and build relationships with plant spirits through dreams seen during a training process called samá. Since they comprehend the process of building relationships with plant spirits by interpreting their dreams, dream interpretation serves as the medium through which the onayas learn how to build relationships with plant spirits, ultimately acquiring the healing capacity to aid others. Focusing on this role of dreams, this study connects an onaya's interpretations of dreams seen during samá to Shipibo cosmology, and examines the onaya-plant spirit relationship formed in dreams through the lens of their cosmological beliefs. The analysis reveals a wide variety of relationships in which the onayas personalize each plant spirit while differentiating its unique representations.